Opposing effects of HIF1α and HIF2α on chromaffin cell phenotypic features and tumor cell proliferation: Insights from MYC‐associated factor X. Issue 9 (7th April 2014) - Qin, Nan; de Cubas, Aguirre A.; Garcia‐Martin, Ruben; Richter, Susan; Peitzsch, Mirko; Menschikowski, Mario; Lenders, Jacques W.M.; Timmers, Henri J. L. M.; Mannelli, Massimo; Opocher, Giuseppe; Economopoulou, Matina; Siegert, Gabriele; et al.
<x xml:space="preserve">Abstract</x> Pheochromocytomas and paragangliomas (PPGLs) are catecholamine‐producing chromaffin cell tumors with diverse phenotypic features reflecting mutations in numerous genes, including MYC‐associated factor X (MAX). To explore whether phenotypic differences among PPGLs reflect a MAX‐mediated mechanism and opposing influences of hypoxia‐inducible factor (HIF)s HIF2α and HIF1α, we combined observational investigations in PPGLs and gene‐manipulation studies in two pheochromocytoma cell lines. Among PPGLs from 140 patients, tumors due to MAX mutations were characterized by gene expression profiles and intermediate phenotypic features that distinguished these tumors from other PPGLs, all of which fell into two expression clusters: one cluster with low expression of HIF2α and mature phenotypic features and the other with high expression of HIF2α and immature phenotypic features due to mutations stabilizing HIFs. Max‐mutated tumors distributed to a distinct subcluster of the former group. In cell lines lacking Max, re‐expression of the gene resulted in maturation of phenotypic features and decreased cell cycle progression. In cell lines lacking Hif2α, overexpression of the gene led to immature phenotypic features, failure of dexamethasone to induce differentiation and increased proliferation. HIF1α had opposing actions to HIF2α in both cell lines, supporting evolving evidence of their differential actions on tumorigenic processes via a MYC/MAX‐related pathway. Requirement of a fully functional MYC/MAX complex to facilitate differentiation explains the intermediate phenotypic features in tumors due to MAX mutations. Overexpression of HIF2α in chromaffin cell tumors due to mutations affecting HIF stabilization explains their proliferative features and why the tumors fail to differentiate even when exposed locally to adrenal steroids.